A Política Invade A Cena: Vida Teatral No Rio De Janeiro Entre 1831 E 1848. - Sampaio, Josiane Nunes Machado [UNIFESP] (2018)
This Research Sought To Analyze The Dynamics Of Theater Culture In The City Of Rio De Janeiro Between 1831 And 1848. The Years Of Regency, With The Independent Country Less Than Ten Years Ago, Was A Space Of Both Political And Artistic Experiences. In A Period Marked By The Emergence Of Several Political Projects And The Fierce Public Opinion In The Press, The Theater Was Present - For Example With The Revolt In The Theater In 1831. Politics Was In Dialogue With The Many Theatrical Repertoires Of The Time, And In The 1840 The Debate Remained Intense. The Theater Was A Space For Civic Celebrations, With Its Spectacles Contemplated By A Diverse Audience, Who In Dialogue With The Scene, Expressed Personal And Collective Demands Of Their Time. Far From Meaning Only A Space Of Fun And Entertainment, The Theater Was Configured As A Space Of Political Sociability, Where The Daily Life Of The City Was Staged, Intense Disputes Over Power, The Diffusion Of Ideas, The Desire To See And Be Seen, The Intertwining Of Publi